PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DI WILAYAH GUGUS I KAPANEWON PANJATAN - Padmi Andarini; Rejokirono; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The objective of this research is to examine the impact of the principal's leadership, work discipline, and work environment on teacher performance in the Cluster I Kapanewon Panjatan region. A quantitative approach is used in this study. This study's population and sample consisted of 64 elementary school teachers from the Cluster I Kapanewon Panjatan area. The data collection technique uses a questionnaire as a data collection tool. The questionnaire is in the form of a statement with a choice of answers that have been provided on a Likert scale. Multiple linear regression analysis techniques were used in the data analysis. The results showed that the value of Fcount > Ftable had a significance level of less than 0.05. This means that there is a positive influence of the principal's leadership, work discipline, and work environment on teacher performance. Judging from the effective contribution and relative contribution, work discipline has the most dominant influence, followed by the principal's leadership and the work environment. Partially, there is a positive and significant influence between work discipline and the leadership of the school principal on teacher performance. While the work environment has no significant effect on teacher performance, From the results of the analysis, it can be concluded that the variables of the principal's leadership, work discipline, and work environment simultaneously have a positive effect on teacher performance in the Cluster I Kapanewon Panjatan area.